Hyperbaric oxygen therapy: Therapeutic role in various cases – A case series - Thenmozhi MD; Sivakumar S; Sethuraja K; Meera SS (Asian Journal of Medical Sciences, 2023)
Hyperbaric oxygen therapy (HBOT) is an adjuvant novel non-invasive treatment technique in the field of plastic surgery for treating different wounds. This technique utilizes 100% oxygen at pressures above the atmospheric pressure. In our study, we are discussing about eight different cases in the field of plastic surgery. HBOT plays an important role in the treatment for different pathological conditions. It involves a hundred percent breathing of oxygen in a closed chamber for a certain period of time. HBOT main mechanism of action is hyper oxygenation but also enhances the immunity by antimicrobial properties and improves stem cell production.